1985
DOI: 10.1007/bf00395975
|View full text |Cite
|
Sign up to set email alerts
|

Action of ultraviolet radiation (UV-B) upon cuticular waxes in some crop plants

Abstract: The surface structure and composition of surface lipids were examined in leaves of barley, bean, and cucumber seedlings grown in a growth chamber under white light and low levels of ultraviolet (UV-B; 280-320 nm) radiation. The cuticular wax of cucumber cotyledons and bean leaves appeared as a thin homogeneous layer, whereas on barley leaves crystal-like structures could be observed under these irradiation conditions. Principally, the amount of cuticular wax found in barley leaves was five times greater than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
1
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 37 publications
6
61
1
1
Order By: Relevance
“…Most compounds found in our leaf surface chloroform extracts had been reported as cuticular waxes or components of the cell membrane of leaves, fruits and seeds of cucumber (Steinm€ uller & Tevini , 1985;Akihisa et al, 1986Akihisa et al, , 1988Hartmann, 1998;Chun et al, 2006). Our results showed that high levels of C. tropicale colonization did not cause significant changes in the composition of cuticular waxes of leaves.…”
Section: Researchsupporting
confidence: 50%
“…Most compounds found in our leaf surface chloroform extracts had been reported as cuticular waxes or components of the cell membrane of leaves, fruits and seeds of cucumber (Steinm€ uller & Tevini , 1985;Akihisa et al, 1986Akihisa et al, , 1988Hartmann, 1998;Chun et al, 2006). Our results showed that high levels of C. tropicale colonization did not cause significant changes in the composition of cuticular waxes of leaves.…”
Section: Researchsupporting
confidence: 50%
“…1), early shoot development (Cape & Percy, 1993) and lower shade tolerance relative to other species (Farrar, 1995). Steinmuller & Tevini (1985), Tevini & Steinmuller (1987), with soybean and Barnes et al (1994Barnes et al ( , 1996 with tobacco, observed a shift toward shorter chain lengths with increased u.v.-B. No effect of u.v.-B on short-to long-chain length homologue ratios was recorded in this study.…”
Section: supporting
confidence: 41%
“…Wax composition in conifers is product of genetic make up (Percy, McQuattie & Rebbeck, 1994) and environmental factors (Gunthardt-Goerg, 1987 ;Cape & Percy, 1993) such as light quality and quantity, temperature and relative humidity. Although it is unresolved whether the cuticle plays any significant role in protecting the plant against u.v.-B, wax chemical composition has been shown to be altered by elevated u.v.-B in a range of crop species such as tobacco (Barnes et al, 1994(Barnes et al, , 1996, pea (Gonzalez et al, 1997), cucumber, bean, and barley (Steinmuller & Tevini, 1985). Recent evidence suggests that there is a critical level for u.v.-B effects on wax biosynthesis in at least one broadleaf tree species, sugar maple (Acer saccharum) (Gordon, Percy & Riding, 1998).…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…V. faba flower wax was characterized by high levels of C 22 alcohol (Griffiths et al, 1999), in contrast to either C 26 or C 30 alcohols in leaf waxes of the closely related Fabaceae spp. Phaseolus vulgaris (Steinmüller and Tevini, 1985), Medicago truncatula (Zhang et al, 2005), and Pisum sativum (Gniwotta et al, 2005; the composition of V. faba leaf wax has not been reported yet). Arabidopsis flower wax is dominated by C 29 alkane (Shi et al, 2011), shorter than the prevalent C 31 homolog in leaves (Jenks et al, 1995) but similar to inflorescence stems and siliques (Todd et al, 1999).…”
Section: Discussionmentioning
confidence: 99%